A Linear Difference Scheme for Dissipative Symmetric Regularized Long Wave Equations with Damping Term. (30th November 2010) - Hu, Jinsong; Xu, Youcai; Hu, Bing
Abstract : We study the initial-boundary problem of dissipative symmetric regularized long wave equations with damping term by finite difference method. A linear three-level implicit finite difference scheme is designed. Existence and uniqueness of numerical solutions are derived. It is proved that the finite difference scheme is of second-order convergence and unconditionally stable by the discrete energy method. Numerical simulations verify that the method is accurate and efficient.